IMPACT OF THE RECENT REFORMS ON INDIAN ARBITRATION LAW - R. Moonka; S. Mukherjee (BRICS Law Journal, 2017)
In order to give effect to the UNICITRAL Model Law on Arbitration and due to radical change in its economy as the result of the 1991 New Economic Policy (NEP) India enacted the 1996 Arbitration & Conciliation Act. This Act provides a pragmatic legal basis for resolution of commercial disputes outside the court procedures. It circumscribes the older laws and consolidates multiple legal norms dealing with arbitration. However, the experiences in application of this Act for the last 20 years suggest that it needs to be amended as it contains serious drawbacks primarily due to poor legal technique which necessitated excessive judicial interventions and judicial overreach having led to resentment among those willing to resort to alternative dispute resolution under this Act while keeping the seat of Arbitration in India. Several attempts were made by the successive governments aiming at amending the 1996 Act. Yet all those attempts failed. Finally the present Union Government under the leadership of the Prime Minister Mr. Narendra Modi was able to bring in sweeping changes in existing arbitration law. These changes were carried out with the commitment of the Government in doing business in India through the Ordinance route and proper legislative procedures which finally led to the amendments having come into force on January 1, 2016. This paper attempts to analyse the key changes brought through the 2015 Amendment Act and their impact on the application of arbitration law in India. Moreover, the authors overview the prospects of India to acquire the preferred position in International Commercial Arbitration in the future as envisioned by the present Modi Government.